Criteria for Legal Subject Proficiency in The Sale and Purchase Deed - Wahyuningsih, Ratna Tri (Riviera Publishing, 2024)
The purpose of this study is to analyze the criteria of legal subjects' proficiency in the sale and purchase deed from the perspective of Article 39, paragraph (1) of the Notary Position Law, Article 7, paragraph (1) of the Marriage Law, Article 1 paragraph (1) of the Child Protection Law and Article 1330 of the Civil Code and the legal implications of the sale and purchase deed carried out by subjects who are not legally competent. The method used in this study is a normative legal method with analysis in a literature study on a problem of conflict between Article 39 of the Notary Position Law, Article 7 of the Marriage Law, Article 1 of the Child Protection Law and Article 1330 of the Civil Code. The results showed the criteria for the proficiency of legal subjects on the sale and purchase deed in the Notary Position Law of at least 18 (eighteen) years old or married, in the Child Protection Law states that the child is someone who is not yet 18 (eighteen) years old, the Marriage Law is marriage allowed if both a man and a woman are 19 (nineteen) years old. In addition, the proficiency criteria according to the Civil Code are 21 (twenty-one) years old or married. The implication is that the sale and purchase deed carried out by an incompetent legal subject results in the sale and purchase deed being cancelled because, basically, the validity of an agreement can be fulfilled with subjective conditions that affect the ability to make agreements. The conclusion of the above problem is that there are differences in setting the age limit of proficiency in various laws and regulations such as the Notary Position Law, Child Protection Law, Marriage Law, and Civil Code. The Notary Office Law stipulates that the age limit for proficiency is 18 years. This difference in regulation triggers differences in perception and legal uncertainty in the age limit of being able to perform legal acts, the need for unification of perceptions and harmonization of laws and regulations related to the definition of the age limit of competence and legal implications for the sale and purchase deed carried out by incompetent subjects have revocable consequences on Deeds made can be cancelled at the will of one of the parties who feel aggrieved by the agreement in the sale and purchase deed.